STRUCTURAL AND FUNCTIONAL DESCRIPTION OF GALL-BLADDER AND BILE DUCTS AT THE FUNCTIONAL DISORDERS, INFLAMMATORY AND NEOPLASTIC PROCESSES FROM THE DATA OF SONOGRAPHIC EXAMINATION - Рижик, В. М.; Перцович, Ю. В.; Воронич-Семченко, Н. М.; Багрій, М. М.; Гудз, Т. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The review of literature of structural and functional description of gall-bladder and bile ducts at the functional disorders, inflammatory and neoplastic processes from data of sonographic examination is presented in the article. The diagnostic criterion of gall-bladder disfunction is the evaluation of it's contraction ability; chronic non-calculous cholecystitis – the assessment of the changes of wall and shape of gall-bladder; chronic calculous cholecystitis – the presence of calculi in gall-bladder and changes of it's wall; polypoid lesions of gall-bladder – the quantity and size of lesion, the type of it’s pedicle, condition of gall-bladder's wall; tumors of bile ducts – the visualization of tumor, symptoms of bile ducts' hypertension, invasion by tumor, presence of metastases.